Gummy Mandjah (Honey, Tamarind, Red Ginger) on Emesis in Pregnant Women - Huzaima, Huzaima; Sari, Diani Mega; Razak , Rifka Atika (Biomedical Journal of Indonesia, 2025)
Introduction. One of the discomforts that mothers frequently experience during the start of pregnancy is emesis gravidarum, which is characterized by nausea and vomiting. The welfare of the mother and child will be impacted if emesis episodes are not handled right away. Herbal remedies like red ginger, tamarind, and honey can help people stay healthy. The purpose of this study is to examine how “Gummy Mandjah” can help pregnant women experience less nausea. Methods. This study used a pre-experimental research design, one group pretest posttest. Giving gummy made from honey, tamarind, and red ginger to 20 pregnant women who met the inclusion criteria, sampling technique using simple random sampling, Gummy was given for 14 days with a dose of 2 times a day and then assessed using the PUQE score. Results. The results obtained showed that there was a decrease in the frequency of emesis after consuming gummy with an average difference of 0.60. Data analysis used a paired sample t-test and showed that there was an effect of giving gummy on reducing emesis with a p-value of 0.001 < 0.05. Conclusion. Honey, tamarind, and ginger can be an option to overcome nausea and vomiting in pregnant women. These ingredients are easy to obtain, practical to process, and have minimal side effects. With gummy innovations or other forms, it can make it easier for pregnant women to consume them and reduce the dominant smell and taste of each ingredient that can trigger mothers not to want to consume them.